Характеристики отопительного периода в г. Перми и их временные изменения (Географический вестник=Geographical bulletin, 2017)
Рассмотрены временные изменения статистических характеристикотопительного периода в г. Перми. Выявлено, что первая часть отопительногопериода характеризуется нулевым трендом. Общая продолжительностьотопительного периода удлиняется за счет смещения даты его окончания на болеепозднее время. Тренд средней температуры отопительного периодаположительный. Наибольший рост температуры наблюдается в последние 15 лет.CHARACTERISTICS OF THE HEATING PERIOD IN PERM CITY AND THEIR TIME CHANGESTime changes of statistical characteristics of the heating period in Perm are considered. It is revealed that the first part of the heating period is characterized by a zero trend. The general duration of the heating period is extended at the expense of displacement of date of its termination for later time. The trend of average temperature of the heating period is positive; greatest growth of temperature is observed for last 15 years.